Genotyping Based on CRISPR Loci Diversity and Pathogenic Potential of Diarrheagenic Escherichia coli - Bai, Zhiye; Zhang, Shiqin; Wang, Xiang; Aslam, Muhammad Zohaib; Wang, Wen; Li, Hongmei; Dong, Qingli (Frontiers in Microbiology, 2022)
Diarrheagenic Escherichia coli (DEC) can cause epidemic diarrhea worldwide. The pathogenic potential of different strains is diverse and the continuous emergence of pathogenic strains has brought serious harm to public health. Accurately distinguishing and identifying DEC with different virulence is necessary for epidemiological surveillance and investigation. Clustered regularly interspaced short palindromic repeats (CRISPR) typing is a new molecular method that can distinguish pathogenic bacteria excellently and has shown great promise in DEC typing. The purpose of this study was to investigate the discrimination of CRISPR typing method for DEC and explore the pathogenicity potential of DEC based on CRISPR types (CT). The whole genome sequences of 789 DEC strains downloaded from the database were applied CRISPR typing and serotyping. The D value (Simpson’s index) with 0.9709 determined that CRISPR typing had a higher discrimination. Moreover, the same H antigen strains with different O seemed to share more identical spacers. Further analyzing the strains CRISPR types and the number of virulence genes, it was found that there was a significant correlation between the CRISPR types and the number of virulence genes (p < 0.01). The strains with the largest number of virulence genes concentrated in CT25 and CT56 and the number of virulence genes in CT264 was the least, indicating that the pathway potential of different CRISPR types was variable. Combined with the Caco-2 cell assay of the laboratory strains, the invasion capacity of STEC strains of different CRISPR types was different and there was no significant difference in the invasion rate between different CRISPR type strains (p > 0.05). In the future, with the increase of the number of strains that can be studied experimentally, the relationship between CRISPR types and adhesion and invasion capacities will be further clarified.